In-situ formation of Ti-Mo biomaterials by selective laser melting of Ti/Mo and Ti/Mo2C powder mixtures: A comparative study on microstructure, mechanical and wear performance, and thermal mechanisms. (10th July 2022) - Shi, Qimin; Yang, Shoufeng; Sun, Yi; Gu, Yifei; Mercelis, Ben; Zhong, Shengping; Van Meerbeek, Bart; Politis, Constantinus
Highlights: Compare SLM of Ti/Mo and Ti/Mo2 C powder mixtures to prepare Ti-Mo biomaterials. Explore thermal mechanisms behind metallurgical differences of Ti-Mo biomaterials. Reach low moduli in both in-situ Ti-7.5Mo-2.4TiC composites and Ti-7.5Mo alloys. Reach 12.1% higher strength in Ti-7.5Mo-2.4TiC composites than Ti-7.5Mo alloys. Reach a 36% lower wear rate in Ti-7.5Mo-2.4TiC composites than Ti-7.5Mo alloys. Abstract: Ti-Mo alloys/composites are expected to be the next-generation implant material with low moduli but without toxic/allergic elements. However, synthesis mechanisms of the Ti-Mo biomaterials in Selective Laser Melting (SLM) vary according to raw materials and fundamentally influence material performance, due to inhomogeneous chemical compositions and stability. Therefore, this work provides a comparative study on microstructure, mechanical and wear performance, and underlying thermal mechanisms of two promising Ti-Mo biomaterials prepared by SLM but through different synthesis mechanisms to offer scientific understanding for creation of ideal metal implants. They are (i) Ti-7.5Mo alloys, prepared from a conventional Ti/Mo powder mixture, and (ii) Ti-7.5Mo-2.4TiC composites, in-situ prepared from Ti/Mo2 C powder mixture. Results reveal that the in-situ Ti-7.5Mo-2.4TiC composites made from Ti/Mo2 C powder mixture by SLM can produce 61.4% more β phase and extra TiC precipitates (diameter below 229.6 nm) than the Ti-7.5Mo alloys. The fine TiC not only contributes to thinner and shorter β columnar grains under a large temperature gradient of 51.2 K/μm but also benefits material performance. The in-situ Ti-7.5Mo-2.4TiC composites produce higher yield strength (980.1 ± 29.8 MPa) and ultimate compressive strength (1561.4 ± 39 MPa) than the Ti-7.5Mo alloys, increasing by up to 12.1%. However, the fine TiC with an aspect ratio of 2.71 dominates an unfavourable rise of elastic modulus to 91.9 ± 2 GPa, 44.7% higher than the Ti-7.5Mo alloys, which, nevertheless, is still lower than the modulus of traditional Ti-6Al-4V. While, TiC and its homogeneous distribution benefit wear resistance, decreasing the wear rate of the in-situ Ti-7.5Mo-2.4TiC composites to 6.98 × 10 −4 mm 3 N −1 m −1, which is 36% lower than that of the Ti-7.5Mo alloys. Therefore, although with higher modulus than the Ti-7.5Mo alloys, the SLM-fabricated in-situ Ti-7.5Mo-2.4TiC composites can expect to provide good biomedical application potential in cases where combined good strength and wear resistance are required. Graphical abstract: Image, graphical abstract